Dispersão de traçador em medições de vazões em tubulações - Roldão, João Sérgio Fajardo (1973)
This work resulted from a need to measure flow rates in the cooling system of a rubber factory (FABOR) and in the water supply system of whole petrochemical complex in Duque de Caixas, State of Rio de Janeiro (mainly REDUC refinery an FABOR factory). Measurements were perfomed by the so-called Peak-to-Peak method with two completely independed measuring systems. It has been shown than an accuracy better than one percent is easily obtainable by this method for the flow velocity measurement. Overall accuracy of the flow rate depends finally on the accuracy of the cross-section area of the pipeline. A new, improved, method of interpretation has been proposed and a complete measurement procedure worked out. Analyse of the dispersion coefficient showed a very good agreement with theoretical value for a smooth pipeline, and a considerable increase of its value for pipelines with bends, valves, etc. Obtained real values of the dispersion coefficient were already used for the planning of other similar works. Analyse of the measured dispersion curves (peaks) seems to indicate that a better theoretical description is obtained when a new solution of the dispersion equation is applied.